2010
DOI: 10.1186/1471-2407-10-419
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of tumor necrosis factor-α in the upregulation of CXCR4 expression in gastric cancer induced by Helicobacter pylori

Abstract: BackgroundH. pylori, whose infection increases tumor invasiveness and metastasis, is generally labelled as the strongest risk factor for the development of gastric cancer. It appears not to be a coincidence that there is also an overexpression of CXCR4 and an obvious involvement in gastric cancer metastasis. The aim of this study attempts to investigate and further to establish a link between them. With H. pylori being a potent inducer of TNF-α, whether TNF-α, a tumor promoter, is involved in the induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 30 publications
5
46
0
Order By: Relevance
“…Finally, H. pylori can induce CXCR4 expression in GC by upregulation of TNF-a which leads to a higher migration rate in epithelial cell lines [65]. These results deliver valuable insights into GC biology that can be used for the development of new therapeutic agents.…”
Section: Differential Gene Regulation In Gcmentioning
confidence: 94%
“…Finally, H. pylori can induce CXCR4 expression in GC by upregulation of TNF-a which leads to a higher migration rate in epithelial cell lines [65]. These results deliver valuable insights into GC biology that can be used for the development of new therapeutic agents.…”
Section: Differential Gene Regulation In Gcmentioning
confidence: 94%
“…H. pylori infection has been reported to increase tumor invasion and metastasis. In this context, H. pylori increased CXCR4 expression in gastric cancer through increased secretion of TNF-α [180]. Besides the expression of CXCR4 by gastric tumor cells, CXCR4 has also been found in leukocytes and microvascular blood vessels, confirming that SDF-1 binds to endothelial cells (Table 2) [174].…”
Section: Esophageal Cancermentioning
confidence: 66%
“…Models with TNF-α-deficient mice have revealed that it is one of the essential cytokines for gastric cancer promotion, along with IL-1 and IL-6 [48]. High TNF-α mRNA expression has been reported in gastric cancer cases [49], as well as in gastric lesion cases such as peptic ulcers [50], chronic gastritis, intestinal metaplasia, and dysplasia [51], whether associated with H. pylori infection or not. Thus, these data corroborate our results.…”
Section: Discussionmentioning
confidence: 98%